LITERATURAS NATIVAS NA EDUCAÇÃO BÁSICA: uma possibilidade de desobediência epistêmica - Ivonete Nink Soares (2024)
The colonization of Pindorama, a Tupi-Guarani term used by native peoples of the coastal region to refer to what we now call Brazil, left profound marks on our culture and society. Since then, the colonialities of being, knowledge, and power have persisted in Brazilian society and, notably, within the school environment. Many aspects of European culture were overvalued, causing the erasure and devaluation of the country’s diverse identities, especially those of marginalized groups such as native peoples. For centuries, formal education was restricted to the dominant classes, with textbooks and materials reflecting only the colonizers’ perspectives. However, in recent decades, minority narratives, especially those authored by individuals who identify with an Indigenous ethnicity, have started to be incorporated into learning environments, opening up space for new historical and cultural perspectives. On March 10, 2008, the Law 11.645 made it mandatory to teach the histories and cultures of original peoples in the national school curriculum, with emphasis on arts, literature, and history. This legislation created space in school curricula for the revision of cultural and historical issues that had previously been silenced. In this context, this study, grounded in applied linguistics, aims to reflect on how working with native literatures in the teaching of Portuguese language and literature in basic education, especially in high school, can contribute to constructing a new perspective on the identities of the original peoples of Brazil. The study also seeks to challenge myths, beliefs, prejudices, and stereotypes rooted in society while promoting epistemic disobedience within the educational field. To achieve this, this qualitative, applied, and exploratory research adopts an action-research methodology. The data generation includes the application of two questionnaires (initial and final) and the development of a decolonial didactic sequence utilizing books of native literature. These activities were carried out with 30 students in a second-year high school class at a public school in Porto Velho-RO, to observe the impacts of Law 11.645/08, implemented over 12 years ago. An interpretive analysis was conducted based on the students’ comments about how they perceive themselves and others (the native subject), guided by the following questions: What does it mean to be Indigenous? What defines a person as Indigenous? With this research, I aim to contribute to a more inclusive and critical approach to teaching Portuguese language and literature, challenging prejudices and promoting a deeper, contextualized understanding of the identities and cultures that constitute Brazil. Keywords: Epistemicide. Epistemic disobedience. Native literatures. Portuguese language teaching. Basic Education.